2021
DOI: 10.21203/rs.3.rs-378418/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breast-Conserving Therapy is Associated with Better Survival than Mastectomy in Early-Stage Breast Cancer: A Propensity Score Analysis

Abstract: Background: Recent retrospective studies have reported that breast-conserving therapy (BCT) led to improved overall survival (OS) than mastectomy in some populations. We aimed to compare the efficacy of BCT and mastectomy using the SEER database. Methods: Between 2010 and 2015, 99,790 eligible patients were identified. We included early-stage breast cancer patients with 5cm or smaller tumors and three or fewer positive lymph nodes in our study. We compared the OS results among patients with BCT and mastectomy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…If such endocrine changes were induced by mastectomy in breast cancer patients, it may be reflected in their long-term outcomes relative to patients undergoing lumpectomy. If such a phenomenon existed, it could help shed light on the curious finding that most retrospective analyses since the previously-mentioned pioneering randomized controlled trials have found improved overall survival or disease-specific survival with lumpectomy and radiation relative to mastectomy (13,(16)(17)(18)(19)(20)(21)(22)(23). A 2013 retrospective analysis from the California Cancer Registry suggested that the discrepancy in overall survival may be related to a higher burden of non-fatal comorbidities among patients undergoing mastectomy relative to lumpectomy with radiation (13).…”
Section: Introductionmentioning
confidence: 99%
“…If such endocrine changes were induced by mastectomy in breast cancer patients, it may be reflected in their long-term outcomes relative to patients undergoing lumpectomy. If such a phenomenon existed, it could help shed light on the curious finding that most retrospective analyses since the previously-mentioned pioneering randomized controlled trials have found improved overall survival or disease-specific survival with lumpectomy and radiation relative to mastectomy (13,(16)(17)(18)(19)(20)(21)(22)(23). A 2013 retrospective analysis from the California Cancer Registry suggested that the discrepancy in overall survival may be related to a higher burden of non-fatal comorbidities among patients undergoing mastectomy relative to lumpectomy with radiation (13).…”
Section: Introductionmentioning
confidence: 99%